Decadal Characterization of Indo-Pacific Ocean Subsurface Temperature Modes in SODA Reanalysis - Vargas-Hernández , José Mauro (2015)
Studies of decadal-to-multidecadal ocean subsurface temperature variability are fundamental to improving the understanding of low-frequency climate signals. The present study uses the Simple Ocean Data Assimilation (SODA) version 2.2.4 product for the period 1950–2007 to identify decadal modes of variability that characterize the upper Indo-Pacific Ocean temperature structure (5–466-m depth). An empirical orthogonal function (EOF) analysis of the 10-yr low-pass filtered temperature field applied across four depths shows that the dominant mode is characterized by a long-term temperature trend, with warming at the surface and cooling at the thermocline depth connecting the tropical western Pacific with the southern Indian Ocean via the Indonesian Seas. EOF analysis of the detrended 10-yr filtered temperature data and correlation analyses of the EOF time series with established large-scale climate indices identified the interdecadal Pacific oscillation as EOF1, the North Pacific Gyre Oscillation as EOF2, and the decadal component of ElNiñoModoki as EOF3 (respectively,modes 2, 3, and 4 of the nondetrended data). EOF2 identifies the Atlantic multidecadal oscillation when the analysis is applied to sea surface temperature anomalies only, suggesting that the surface is forced dominantly by fluxes associated with global-scaleweather patterns, while the subsurface is dominantly forced by internal dynamics of the Pacific Ocean. This paper demonstrates that the decadal-to-interdecadal temperature variability in SODA has a pronounced vertical extension through the upper ocean. The upper thermocline accounts for most of the variance in the analysis. These results reinforce the importance of examining the subsurface ocean in climate dynamics studies that seek to understand the ocean’s role.